2010
DOI: 10.1590/s0103-97332010000100009
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of structural, electronic and elastic properties of Nb4AlC3

Abstract: Using First-principles calculations, we have studied the structural, electronic and elastic properties of Nb 4 AlC 3 , a new compound belonging to the MAX phases. Geometrical optimization of the unit cell is in good agreement with the experimental data. The effect of high pressures, up to 20 GPa, on the lattice constants shows that the contractions are higher along the c-axis than along the a-axis. We have observed a quadratic dependence of the lattice parameters versus the applied pressure. The band structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 37 publications
(41 reference statements)
2
35
0
Order By: Relevance
“…A plane-wave basis set was used to solve the KohnSham equations in the pseudopotential implementation of the DFT-LDA. The major advantages of this approach are: the ease of computing forces and stresses; good convergence control with respect to all employed computational parameters; favourable scaling with number of atoms in the system and the ability to make cheaper calculations by neglecting core electrons [29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A plane-wave basis set was used to solve the KohnSham equations in the pseudopotential implementation of the DFT-LDA. The major advantages of this approach are: the ease of computing forces and stresses; good convergence control with respect to all employed computational parameters; favourable scaling with number of atoms in the system and the ability to make cheaper calculations by neglecting core electrons [29].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, at low temperatures the Debye temperature calculated from elastic constants is the same as that determined from specic heat measurements. One of the standard methods to calculate the Debye temperature (θ D ) is from elastic constants data, since θ D may be estimated from the average sound velocity, v m by the following equation [29]:…”
Section: Calculation Of Debye Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, under loads above 4.9 N, the hardness is higher for the top surface than the side surface. Bouhemadou [34] confirmed that the compressibility of Nb 4 AlC 3 was greater along the c-axis than along the a-axis. Because the indent is the result of compressive, shearing and tensile stresses, higher hardness is expected for the textured side surface.…”
Section: Resultsmentioning
confidence: 84%
“…Electrical conductivity measurements revealed higher values perpendicular (0.81 × not from Al electrons, owing to a scooping effect resulting from the presence of the Nb d states [34]. Therefore, Al electrons should not significantly contribute to the conduction.…”
Section: Resultsmentioning
confidence: 93%